An Analysis of Supply Chain Macro-Strategies in the Context of Industry 4.0 with a System Dynamics Approach (The Case of: Iran's Steel Supply Chain) - Sima Motallebi; Mostafa Zandieh; Akbar Alem Tabriz (Journal of Systems Thinking in Practice)
Forward-thinking decisions and adopting cutting-edge technologies typically influence the management of large, multi-level supply chains. Given the various raw materials, semi-finished products, and final goods in these multi-level supply chains, balancing imports and exports is one of the most significant challenges and macro-level issues facing countries. System dynamics simulation is a powerful tool for analyzing macro-level issues, as it can predict future system behavior based on current conditions. In this research, Iran's steel supply chain was selected as a case study to assess future trends at the macro level under the influence of Industry 4.0. Industry 4.0 encompasses a range of innovative technologies that can improve supply chain efficiency. For this purpose, AnyLogic software was used to simulate the model. According to the system dynamics simulation results, keeping a balance between supply and demand at each stage of the supply chain plays a crucial role in increasing efficiency and profitability. Additionally, macro-level policies such as budget allocation, export rate, and support for investments in various parts of the supply chain directly impact this chain's performance. Sensitivity analysis revealed that increasing the budget and production capacity in the direct reduced iron (DRI) and crude steel sectors has a greater impact on the overall profitability of the chain, and exporting crude steel can be a significant way to increase revenue and foreign exchange earnings for the country.